A D-shaped elliptical hollow core fiber SPR sensor. Issue 1 (1st October 2022) - Khanikar, Tulika; Singh, Vinod Kumar
Abstract : A D-shaped elliptical hollow core fiber surface plasmon resonance (SPR) sensor is proposed and analyzed here using gold and titanium oxide (TiO2 ) layer. The fiber geometry consists of a doped elliptical core with a concentric central elliptical air hole. A finite element method-based simulation software COMSOL Multiphysics is used for numerical analysis. Both gold and TiO2 layers are optimized. The sensor responds over a wide range of refractive index (RI) from 1.33 to 1.40. The average sensitivity obtained for the designed sensor is 4142.85nm/RIU (RI Unit) whereas that for a single mode fiber (SMF) is only 897.55nm/RIU. So, our designed sensor gives more than 4 times enhanced sensitivity and proves to be a potential alternative of SMF based low cost, compatible SPR sensors by covering the low sensitivity issue suffered by SMF sensors.